Genomic assessment of targets implicated in Rhipicephalus microplus acaricide resistance. - Christina Meiring; Michel Labuschagne (PLoS ONE)
Globally, the prevalence of Rhipicephalus microplus resistance to various acaricides has increased, and there is a need for the identification of molecular markers that can predict phenotypic resistance. These markers could serve as alternatives to the larval packet test (LPT), enabling rapid and accurate monitoring of resistance in these ticks against multiple acaricides. However, many of the historically identified markers are present in isolates from specific countries and their role in acaricide resistance remains unclear. This study aimed to assess these mutations by sequencing genomic regions encoding proteins historically associated with acaricide target site insensitivity and increased acaricide detoxification and comparing resistant and susceptible isolates from eight different countries. Employing a novel multiplex PCR setup developed during the study, the coding regions of 11 acaricide-resistant targets were amplified and sequenced across 37 R. microplus isolates from different locations. The identified mutations, both previously reported and novel, were compared between acaricide-susceptible and acaricide-resistant isolates, phenotypically characterized using the larval packet test or larval immersion test across five acaricide classes. Genotypes were then correlated with available phenotypes, and protein modelling of novel nonsynonymous mutations was conducted to assess their potential impact on acaricide resistance. Previously reported resistance-associated mutations were detected, some of which were present in both resistant and susceptible isolates. Novel mutations emerged from the 11 targets, but distinctions between susceptible and resistant isolates were not evident, except for the prevalent kdr mutation in synthetic pyrethroid-resistant isolates. The quest for predictive molecular markers for monitoring acaricide resistance remains challenging. Nevertheless, by utilizing a representative group of isolates, we determined that several historical mutations were present in both resistant and susceptible isolates. Additionally, the study provides valuable genetic data on acaricide-resistant and susceptible isolates from different geographical regions, focusing on genomic regions implicated in resistance. This baseline data offers a critical foundation for further research and the identification of more reliable molecular markers.